2017
DOI: 10.1016/j.powtec.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shape and surface charge on the sedimentation of spheroidal, cubic and rectangular cuboid particles

Abstract: This study investigated the complex settling behaviour of colloidal particles with varied surface charge and shape factors, of specific relevance to nuclear waste processing. Caesium phosphomolybdate (CPM), zirconium molybdate (ZM) and zirconium citromolybdate (ZMCA) were firstly synthesised, producing spheroidal, cubic and rectangular cuboidal morphologies respectively, and compared to agglomerated titania. While zeta-potential measurements indicated all simulant particles attained low isoelectric points, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
(109 reference statements)
2
13
0
Order By: Relevance
“…For the ZM-a simulant, the cuboidal particles are shown to be around thirty times larger than the CPM with a D50 value of 10 μm. Unsurprisingly, when comparing SEM images ( Figure 1 d), ZM-b displays a larger D50 value than ZM-a with a value of 14 μm, although caution must be taken with light scattering estimations of any non-spherical particles [ 22 ]. In comparison to the literature, the CPM synthesised at 50 °C particle size is within the expected range, [ 21 ] while the D50 for the ZM-a is slightly larger than previously reported [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ZM-a simulant, the cuboidal particles are shown to be around thirty times larger than the CPM with a D50 value of 10 μm. Unsurprisingly, when comparing SEM images ( Figure 1 d), ZM-b displays a larger D50 value than ZM-a with a value of 14 μm, although caution must be taken with light scattering estimations of any non-spherical particles [ 22 ]. In comparison to the literature, the CPM synthesised at 50 °C particle size is within the expected range, [ 21 ] while the D50 for the ZM-a is slightly larger than previously reported [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…ZM has been the focus of several studies within literature, where it has been synthesised for various applications, such as a Technetium-99m generator [ 4 , 5 , 6 , 7 ], a precursor for the formation of the negative thermal expansion material ZrMo 2 O 8 [ 8 , 9 ] and predominately for nuclear waste based studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Clearfield et al [ 24 ] were the first to publish a synthesis route for ZM to characterise its ion exchange properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is well known that the drag force increases as function of projected area which is more important for irregular than spherical shape, especially if this projected area oriented in the direction of fall [41,45]. Thus, the drag force applied to the platelet-like particles is higher than that applied to the spheres, In other words, the displacement of the platelet-like particles is more affected by the drag forces of the medium, and thus their sedimentation rate is reduced with respect to spherical particles.…”
Section: Functionalized Mos 2 Particlesmentioning
confidence: 99%
“…To provide control over the fineness (i.e., the cut size) of the comminuted product conveyed to the burners, coal roller mills apply static or dynamic classifiers [8,20], which classify particles based on their shape, size, and density [21]. The cut size is based on Stokes' law [22] that is only valid for the drag force of a spherical particle [23]. Williams et al [17] found that the classification system of a ring-roller mill for the comminution of densified biomasses followed the Stokes' law, indicated by an increasing sphericity with decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%